2016
DOI: 10.1128/jb.00969-15
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mutational Analyses of Escherichia coli ZapD Reveal Charged Residues Involved in FtsZ Filament Bundling

Abstract: Bacterial cell division is an essential and highly coordinated process. It requires the polymerization of the tubulin homologue FtsZ to form a dynamic ring (Z-ring) at midcell. Z-ring formation relies on a group of FtsZ-associated proteins (Zap) for stability throughout the process of division. In Escherichia coli, there are currently five Zap proteins (ZapA through ZapE), of which four (ZapA, ZapB, ZapC, and ZapD) are small soluble proteins that act to bind and bundle FtsZ filaments. In particular, ZapD forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…This could also be the case for positive regulators of FtsZ assembly, such as ZapD. Indeed, this type of binding model could explain data from Roach et al (37) that showed cross-linking between ZapD and FtsZ core residues. Alternatively, the results from these cross-linking experiments could be due to nonspecific contacts between ZapD and FtsZ resulting from ZapD induced bundling and aggregation of FtsZ molecules.…”
Section: Zapd-ftsz Ctd Interactions Are Mediated By An Unusualmentioning
confidence: 78%
See 2 more Smart Citations
“…This could also be the case for positive regulators of FtsZ assembly, such as ZapD. Indeed, this type of binding model could explain data from Roach et al (37) that showed cross-linking between ZapD and FtsZ core residues. Alternatively, the results from these cross-linking experiments could be due to nonspecific contacts between ZapD and FtsZ resulting from ZapD induced bundling and aggregation of FtsZ molecules.…”
Section: Zapd-ftsz Ctd Interactions Are Mediated By An Unusualmentioning
confidence: 78%
“…Like ZapA, both ZapC and ZapD interact directly with FtsZ and also promote FtsZ protofilament assembly (20,27,28). Structures have recently been obtained for all the Zap proteins and show that, interestingly, despite their overlapping functions, they are structurally distinct (22,26,(35)(36)(37)(38). ZapA and ZapB are coiled-coil proteins that form dimeric or tetrameric structures; ZapB consists almost entirely of an extended coiled coil, whereas ZapA contains N-terminal globular domains in addition to its coiled-coil region (22,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To unveil overall structural similarities with other known structures from PDB, a search using the DALI program was performed (Holm and Rosenstrom, 2010). It showed several structurally similar proteins including (i) cell division protein ZapD from E. coli (5DKO, Z-score 30) (Roach et al, 2016), (ii) the DUF1342 protein (unknown function) from V. parahaemolyticus (2OEZ, Z-score 27), and (iii) Integron cassette protein from V. paracholerae (3JRT, Z-score 8.2) (Sureshan et al, 2013). When we compared our StZapD refined structure with the high Z-score structures (PDB codes 5DKO, 2OEZ, and 3JRT), the r.m.s.…”
Section: Resultsmentioning
confidence: 99%
“…Zaps, which are FtsZ positive regulators, include ZapA, ZapB, ZapC, and ZapD and they are structurally characterized (Ebersbach et al, 2008; Low et al, 2004; Ortiz et al, 2015; Roach et al, 2016). ZapA is well known as a positive regulator of Z-ring formation, which can bind to FtsZ at the globular core directly (Galli and Gerdes, 2012).…”
Section: Introductionmentioning
confidence: 99%